Impact of Frailty and Other Geriatric Syndromes on Clinical Management and Outcomes in Elderly Patients With Non–ST‐Segment Elevation Acute Coronary Syndromes: Rationale and Design of the LONGEVO‐SCA Registry. Issue 7 (30th June 2016) - Alegre, Oriol; Ariza‐Solé, Albert; Vidán, María T.; Formiga, Francesc; Martínez‐Sellés, Manuel; Bueno, Héctor; Sanchís, Juan; López‐Palop, Ramón; Abu‐Assi, Emad; Cequier, Àngel
ABSTRACT: The incidence of acute coronary syndromes (ACS) is high in the elderly. Despite a high prevalence of frailty and other aging‐related variables, little information exists about the optimal clinical management in patients with coexisting geriatric syndromes. The aim of the LONGEVO‐SCA registry (Impacto de la Fragilidad y Otros Síndromes Geriátricos en el Manejo y Pronóstico Vital del Anciano con Síndrome Coronario Agudo sin Elevación de Segmento ST) is to assess the impact of aging‐related variables on clinical management, prognosis, and functional status in elderly patients with ACS. A series of 500 consecutive octogenarian patients with non–ST‐segment elevation ACS from 57 centers in Spain will be included. A comprehensive geriatric assessment will be performed during the admission, assessing functional status (Barthel Index, Lawton‐Brody Index), frailty (FRAIL scale, Short Physical Performance Battery), comorbidity (Charlson Index), nutritional status (Mini Nutritional Assessment–Short Form), and quality of life (Seattle Angina Questionnaire). Patients will be managed according to current recommendations. The primary outcome will be the description of mortality and its causes at 6 months. Secondary outcomes will be changes in functional status and quality of life. Results from this study might significantly improve the knowledge about the impact of aging‐related variables on management and outcomes of elderly patients with ACS. Clinical management of these patients has become a major health care problem due to the growing incidence of ACS in the elderly and its particularities.